Utilization Of Natural Materials As Universal Natural Food Colors Red Yellow Green In The Community Of Sidomulyo Village Biru-Biru District: Pemanfaatan Bahan Alam Sebagai Pewarna Pangan Alami Universal Merah Kuning Hijau Pada Masyarakat Desa Sidomulyo Kecamatan Biru-Biru - Sartika Daulay, Anny; Ridwanto, Ridwanto; Dison Silalahi, Alistraja; Wahyuni, Sri; Indrayani Dalimunthe, Gabena; Fadhilah M, Ihsan (Universitas Haji Sumatera Utara, 2025)
Food coloring is an additional ingredient used to produce food products so they are more attractive to consume. Synthetic food coloring comes from chemicals, can contain dangerous metals and/or benzene rings which have the potential to cause various diseases in humans. Meanwhile, natural dyes are obtained from natural ingredients so they are safer to use. The aim of this community service is to provide understanding to the public about the benefits of plants in the form of fruit, leaves and fruit skins that are no longer used as natural food coloring. This community service (PkM) is carried out by socializing the use of fruit and/or fruit waste, fresh leaves which are commonly found in the community, such as dragon fruit peel as waste. Other ingredients used are turmeric rhizomes and bay leaves, suji leaves and pandan leaves. Socialization of making food coloring materials is carried out using electronic media such as videos. Meanwhile, the explanation of the material is carried out using the presentation and discussion method. Based on the results of the implementation of this PkM, the people of Sidomulyo Village, Biru-Biru District, were very enthusiastic and eager to take part in this activity. The people of Sidomulyo Village can understand and comprehend the dangers of using synthetic dyes and understand the benefits of using natural dyes in food produced in the household. Then in the future, the results of this community service can be applied to products that can be marketed commercially to increase family income.